Enhancing the dipole ring of hexagonal boron nitride nanomesh by surface alloying - Gyula Halasi; Csaba Vass; Ka Man Yu; Gábor Vári; Arnold P. Farkas; Krisztián Palotás; András Berkó; János Kiss; Zoltán Kónya; Martin Aeschlimann; Benjamin Stadtmüller; Péter Dombi; et al. (npj 2D Materials and Applications, 2024)
Abstract Surface templating by electrostatic surface potentials is the least invasive way to design large-scale artificial nanostructures. However, generating sufficiently large potential gradients remains challenging. Here, we lay the groundwork for significantly enhancing local electrostatic fields by chemical modification of the surface. We consider the hexagonal boron nitride (h-BN) nanomesh on Rh(111), which already exhibits small surface potential gradients between its pore and wire regions. Using photoemission spectroscopy, we show that adding Au atoms to the Rh(111) surface layer leads to a local migration of Au atoms below the wire regions of the nanomesh. This significantly increases the local work function difference between the pore and wire regions that can be quantified experimentally by the changes in the h-BN valence band structure. Using density functional theory, we identify an electron transfer from Rh to Au as the microscopic origin for the local enhancement of potential gradients within the h-BN nanomesh.